2017
DOI: 10.1111/tra.12479
|View full text |Cite
|
Sign up to set email alerts
|

Deleting the DAG kinase Dgk1 augments yeast vacuole fusion through increased Ypt7 activity and altered membrane fluidity

Abstract: Diacylglycerol (DAG) is a fusogenic lipid that can be produced through phospholipase C activity on phosphatidylinositol 4,5-bisphosphate [PI(4,5)P2], or through phosphatidic acid (PA) phosphatase activity. The fusion of Saccharomyces cerevisiae vacuoles requires DAG, PA and PI(4,5)P2, and the production of these lipids is thought to provide temporally specific stoichiometries that are critical for each stage of fusion. Furthermore, DAG and PA can be interconverted by the DAG kinase Dgk1 and the PA phosphatase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 97 publications
3
46
0
Order By: Relevance
“…Phosphatidic acid, LPA and DAG are involved in many membrane fusion and membrane fission events, such as fission of Golgi membranes , fission during endocytic transport , vacuole fission and fusion , mitochondrial dynamics , exocytosis , vesicle‐vesicle fusion , myoblast fusion , osteoclast fusion , membrane fusion during sporulation , membrane fusion during fertilization . Fusion of PA‐containing vesicles was studied in Refs .…”
Section: The Role Of Pa In Membrane Fusion and Membrane Fissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphatidic acid, LPA and DAG are involved in many membrane fusion and membrane fission events, such as fission of Golgi membranes , fission during endocytic transport , vacuole fission and fusion , mitochondrial dynamics , exocytosis , vesicle‐vesicle fusion , myoblast fusion , osteoclast fusion , membrane fusion during sporulation , membrane fusion during fertilization . Fusion of PA‐containing vesicles was studied in Refs .…”
Section: The Role Of Pa In Membrane Fusion and Membrane Fissionmentioning
confidence: 99%
“…Phosphatidic acid, LPA and DAG are involved in many membrane fusion and membrane fission events, such as fission of Golgi membranes [140,162,163,[165][166][167][168][169], fission during endocytic transport [170,171], vacuole fission [172] and fusion [132,147,[173][174][175], mitochondrial dynamics [17,40,95,[176][177][178][179][180][181][182][183][184][185], exocytosis [30,40,76,79,125,[186][187][188][189][190][191][192][193][194], vesicle-vesicle fusion [164], myoblast fusion [195,196], osteoclast fusion [197], membrane fusion during sporulation [198][199][200][201], membrane fusion during fertilization [202,203]. Fusion of PA-containing vesicles was studied in Refs [87,…”
Section: The Role Of Pa In Membrane Fusion and Membrane Fissionmentioning
confidence: 99%
“…Furthermore, localization of Dgk1 has not been clearly defined. Dgk1 is an integral membrane protein initially proposed to localize to the ER, although it has recently been found associated with vacuoles …”
Section: Introductionmentioning
confidence: 99%
“…Dgk1 is an integral membrane protein initially proposed to localize to the ER, 29 although it has recently been found associated with vacuoles. 30 DAG is a minor component of eukaryotic membranes. Lipidomic studies of wild-type yeast grown in standard defined medium conditions revealed that DAG represented 4-6 mol% of total lipids.…”
mentioning
confidence: 99%
“…SNARE complex isolation was performed as described previously using GST‐Vam7 . Briefly, 6x fusion reactions were incubated with 85 μg/mL anti‐Sec17 IgG to block priming.…”
Section: Methodsmentioning
confidence: 99%